NR4A1 Regulates Motility of Osteoclast Precursors and Serves as Target for the Modulation of Systemic Bone Turnover. (24th July 2018) - Scholtysek, Carina; Ipseiz, Natacha; Böhm, Christina; Krishnacoumar, Brenda; Stenzel, Martin; Czerwinski, Tina; Palumbo‐Zerr, Katrin; Rothe, Tobias; Weidner, Daniela; Klej, Alexandra; Stoll, Cornelia; Distler, Jörg; et al.
ABSTRACT: NR4A1 (Nur77 or NGFI‐B), an orphan member of the nuclear receptor superfamily, has been identified as a key regulator of the differentiation and function of myeloid, lymphoid, and mesenchymal cells. The detailed role of NR4A1 in bone biology is incompletely understood. Here, we report a role for NR4A1 as novel factor controlling the migration and recruitment of osteoclast precursors during bone remodeling. Myeloid‐specific but not osteoblast‐specific deletion of NR4A1 resulted in osteopenia due to an increase in the number of bone‐lining osteoclasts. Although NR4A1‐deficient osteoclast precursors displayed a regular differentiation into mature osteoclasts, they showed a hyper‐motile phenotype that was largely dependent on increased osteopontin expression, suggesting that expression of NR4A1 negatively controlled osteopontin‐mediated recruitment of osteoclast precursors to the trabecular bone. Pharmacological activation of NR4A1, in turn, inhibited osteopontin expression and osteopontin‐dependent migration of osteoclast precursors resulted in reduced abundance of bone‐resorbing osteoclasts in vivo as well as in an ameliorated bone loss after ovariectomy in mice. This study identifies NR4A1 as a crucial player in the regulation of osteoclast biology and bone remodeling and highlights this nuclear receptor as a promising target for therapeutic intervention during the treatment of osteoporosis. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.